Microdrill stapedotomy for otosclerosis with small and large preoperative air-bone gap: a retrospective comparison of results. (1st September 2020) - Canale, Andrea; Albera, Andrea; Macocco, Francesco; Caranzano, Federico; Albera, Roberto
Abstract: Background: In otosclerosis mixed hearing loss is the most frequent symptom and arises when the focus involves the stapes footplate. Surgeons usually prefer to wait a minimum air-bone gap of 25 – 35 dB before surgery. Objectives: To evaluate the outcome of microdrill stapedotomy for otosclerosis in patients with a preoperative air-bone gap (ABG) <25 dB versus patients with a preoperative gap ≥ 25 dB. Material and methods: For this retrospective study, the outcomes and complications after microdrill stapedotomy were compared between adult patients with a preoperative small ABG ( n  = 127, ABG <25 dB) and those with a large ABG ( n  = 254, ABG ≥25 dB). Results: The postoperative ABG was significantly smaller than the preoperative ABG ( p  < .05) in both groups; there were no differences in complications rates (severe sensorineural hearing loss, footplate fracture or early postoperative vertigo) between the two groups. Conclusions: Our findings show that microdrill stapedotomy is safe and can be performed even in patients with a preoperative small ABG without increasing the risk of sensorineural hearing loss due to inner ear damage.